Osteomielitis crónica con periostitis proliferativa - Conte Neto, Nicolau [UNESP]; Gonçalves, Marcelo [UNESP]; Pereira Filho, Valfrido Antonio [UNESP]; Carvalho, Waldner Ricardo Souza de [UNESP]; Silva, Lucas Martins de Castro (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
Chronic osteomyelitis with proliferative periostitis is a kind of osteomyelitis that is characterized by a great periosteal reaction resulting of low grade stimulation, usually a caries lesion associated a periapical pathology. It affects especially children and young adults, with the mandible as the most common site, usually in the inferior aspect. Clinically presents as a painless hard swelling intra and/or extra-oral. Radiographic aspects include bone layers new formed, parallel to each other and to the underlying cortical surface, giving the characteristic appearance of "onion skin". Treatment includes elimination of the cause, with or without antibiotics, being restored the facial symmetry of patient. The present article is a clinical case report of chronic osteomyelitis with proliferative periostitis affecting a female 11 year old patient, caused by a caries lesion in the left permanent first molar, that was submissed to a exodontia and the facial symmetry of the patient was restored with management.

La osteomielitis crónica con periostitis proliferativa es un tipo de alteración caracterizada por una reacción periosteal exacerbada causada por un estimulo de baja intensidad, generalmente una lesión cariosa con patología periapical asociada. Actúa principalmente en niños y adolescentes con predilección por la región basilar de mandíbula. Clínicamente, se manifiesta a través de un aumento de volumen doloroso intra o extraoral, de consistencia endurecida. Radiográficamente presenta laminas óseas neoformadas, paralelas entre si con superficie cortical, observándose el aspecto típico de "cascara de cebolla". El tratamiento incluye el retiro del factor etiológico con o sin antibioterapia y posterior restablecimiento de la simetría facial del paciente. Este trabajo presenta un caso de osteomielitis crónica con periostitis proliferativa en una paciente de sexo femenino de 11 años de edad, causada por una lesión cariosa en el primer molar inferior izquierdo, quien fue sometida a exodoncia del diente comprometido con posterior restablecimiento de la simetría facial.
Chronic osteomyelitis with proliferative periostitis
Keywords: Osteomyelitis; Proliferative periostitis; Dental caries; Osteomielitis; Periostisis proliferativa; Caries